Impaired autophagy in macrophages promotes inflammatory eye disease. Issue 10 (2nd October 2016) - Santeford, Andrea; Wiley, Luke A.; Park, Sunmin; Bamba, Sonya; Nakamura, Rei; Gdoura, Abdelaziz; Ferguson, Thomas A.; Rao, P. Kumar; Guan, Jun-Lin; Saitoh, Tatsuya; Akira, Shizuo; Xavier, Ramnik; et al.
ABSTRACT: Autophagy is critical for maintaining cellular homeostasis. Organs such as the eye and brain are immunologically privileged. Here, we demonstrate that autophagy is essential for maintaining ocular immune privilege. Deletion of multiple autophagy genes in macrophages leads to an inflammation-mediated eye disease called uveitis that can cause blindness. Loss of autophagy activates inflammasome-mediated IL1B secretion that increases disease severity. Inhibition of caspase activity by gene deletion or pharmacological means completely reverses the disease phenotype. Of interest, experimental uveitis was also increased in a model of Crohn disease, a systemic autoimmune disease in which patients often develop uveitis, offering a potential mechanistic link between macrophage autophagy and systemic disease. These findings directly implicate the homeostatic process of autophagy in blinding eye disease and identify novel pathways for therapeutic intervention in uveitis.